High-throughput synthesis and corrosion behavior of sputter-deposited nanocrystalline Alx(CoCrFeNi)100-x combinatorial high-entropy alloys - Shi, Yunzhu; Yang, Bin; Rack, Philip D.; Guo, Shifeng; Liaw, Peter K.; Zhao, Ying (Materials & design, 2020)
High-entropy alloys (HEAs) are inherently complex and potentially span a vast composition space, making their research and discovery challenging. In the present study, high-throughput synthesis of an Alx(CoCrFeNi)100-x combinatorial material library covering x = 4.5–40 atomic percent Al is achieved, using magnetron co-sputtering. The effects of Al on the microstructure and corrosion behavior are investigated. With the increased amount of Al, crystal-structures of thin films transform from face-centered cubic (FCC) to body-centered cubic (BCC). Both the FCC and BCC thin films demonstrate a uniform elemental distribution. Corrosion characteristics of combinatorial samples immersed in the 3.5 wt% (wt%) NaCl solution are evaluated via electrochemical tests. Complementary X-ray photoelectron spectroscopy analysis reveals the compositional variation of passivated films formed on the sample surface after immersion. The results show that the Alx(CoCrFeNi)100-x HEA thin films possess outstanding corrosion-resistant properties, but the resistance diminishes with the increasing Al content. The decreased corrosion resistance is revealed to be directly related to the constituents of passivated films. [Display omitted] •High-throughput synthesis of Alx(CoCrFeNi)100-x high-entropy alloys is achieved.•The influences of Al on the microstructure and corrosion behavior are evaluated.•Alx(CoCrFeNi)100-x thin films possess outstanding corrosion-resistant properties.